Forests and Our Future: The Path Toward Sustainable Development - Purnomo, Rahmat (Journal of Horizon, 2025)
Forests are essential ecosystems that serve as the foundation of global environmental stability, cultural heritage, and sustainable livelihoods. This research explores the role of forests in advancing sustainable development, using a qualitative descriptive approach based on literature analysis, in-depth interviews, and field observations. The study focuses on forest governance in Indonesia while drawing comparisons to global frameworks such as the Sustainable Development Goals (SDGs) and REDD+ initiatives. Findings reveal a significant gap between policy design and on-the-ground implementation, highlighting the challenges of institutional fragmentation, land tenure insecurity, and competing development priorities. Community-based forest management (CBFM) emerges as an effective strategy when supported by legal recognition and cultural integration, but often lacks sufficient policy support. The study underscores the need for inclusive, rights-based governance models that integrate scientific and Indigenous knowledge, strengthen cross-sectoral coordination, and promote environmental education. Forests must be reimagined not as extractive resources but as vital systems for ecological balance and intergenerational equity.